Corporate governance models and applications in developing economies - Agyemang, Otuo Serebour, 1983-; Ansong, Abraham, 1981-; Agyei-Mensah, Ben Kwame, 1962- (IGI Global, 2019)
"This book examines models of corporate governance and their application in developing economies"--